Customer Preferences for Reliable Power Supply: Using Data on Actual Choices of Back-Up Equipment - Matsukawa, Isamu; Fujii, Yoshifumi (The Review of Economics and Statistics, 1994)
Isamu Matsukawa, Yoshifumi Fujii, Customer Preferences for Reliable Power Supply: Using Data on Actual Choices of Back-Up Equipment, The Review of Economics and Statistics, Vol. 76, No. 3 (Aug., 1994), pp. 434-446